The general comparability of modules and its applications on the ideals of SF-rings - Li, Yan-Wu; Cheng, Hai-Xia; Yin, Xiao-Bin (Zhejiang da xue xue bao. Journal of Zhejiang University. Sciences edition. Li xue ban, 2013)
The general comparability and its characterization of modules on the ideals of SF-rings were studied. Additionally, the problem of matrix diagonalization on comparable ideals was studied and the conditions of correlation matrix which can were diagonalized be obtained, which take advantage of the comparability of ideals on SF-rings.